The Influence of Human Resource Management Practices on Career Satisfaction: Evidence from Malaysia - Hee, Ong Choon; Cheng, Teo Yin; Yaw, Chang Chun; Gee, Wong Vee; Kamaludin, Siti Maryam; Prabhagaran, Jasveena R. (International Review of Management and Marketing, 2016)
The purpose of this study is to examine the relationship between Human Resource Management (HRM) practices (Training and Development, Compensation and Benefit, Performance Management) and career satisfaction. Data was collected through questionnaire from 80 employees of various banks in Johor Bahru, Malaysia. The results of the regression analysis showed that training and development and compensation and benefitwere significantlyrelated to employee career satisfaction. Thefindings suggested that training and development isthe most important factor that influence career satisfaction followed by compensation and benefits. Performance management was found to be not significant in predicting career satisfaction. Keywords: Career Satisfaction; HRM Practices; Training and Development; Compensation and Benefit; Performance Management, Malaysia. JEL Classifications: I25, J28 O15